The Effectiveness of Arbuscular Mycorrhizal Fungi Seed Coating on the Sengon Seed Germination under Drought Stress - Nur Buana, Mursalina; Budi, Sri Wilarso (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2025)
Global warming has caused drought, which is a limiting factor for tree growth. The effect of drought stress can be suppressed by utilizing Arbuscular Mycorrhizal Fungi (FMA) which can be applied through seed coating. The study aimed to determine the response of sengon seed germination to drought stress, the effectiveness of FMA inoculation on sengon seedlings, and the effectiveness of seed coating on sengon seed germination under drought stress. The research was conducted with a two-factor completely randomized design, namely drought stress and FMA inoculation. The results showed that drought stress reduced the germination of sengon seeds. Application of FMA seed coating can increase seed tolerance to drought stress but has no real effect at the 5% level. Inoculation of FMA through seed coating showed higher growth rate and root colonization than inoculation in the planting media, indicating that seed coating has a higher effectiveness in the mechanism of tolerance of sengon seedlings to drought stress.